An Empirical Study on the Status of Work-Life Balance in Oil and Natural Gas Corporation Limited (ONGC) - Singh, Satinder (Prabandhan: Indian Journal of Management, 2015)
Discussion on work-life balance is presently much in demand and both employers and employees are giving it the much needed importance . Much of the growing amount of research into work-life balance reflects the widespread interest in the topic. This study explores the status of work-life balance in Oil and Natural Gas Corporation Limited (ONGC). In order to gain different perspectives on work-life balance in ONGC, the research design comprises of interviews with employees of ONGC, Ahmedabad Asset covering each level of employees - from staff to senior managerial level employees working with various departments with varying work schedules and covering both the genders - male and female employees. The key findings of the research are that the employees of ONGC had obtained a good work-life balance by making mutual adjustments. However, there is a need to develop work-life balance policies customized to individual needs with effective supportive system to reduce work-life conflicts.